Intergenerational disagreements in labor supply and optimal bequest taxation - Hakki Yazici (Central Bank Review (CBR), 2017)
This paper studies optimal taxation of bequests in a model where altruistic parents and their offspring disagree on the offspring's labor supply decision. I show that whenever offspring is too lazy from the parent's perspective and there are income effects on labor supply, optimal policy involves a subsidy on bequests.
Keywords: 330; Intergenerational disagreement; Bequests; Optimal taxation